Microalbuminuria: a potential prognostic marker for acute stroke - Gumbinger, Christoph; Sykora, Marek; Diedler, Jennifer; Ringleb, Peter A.; Rocco, Andrea (Der Nervenarzt, 2012)
IntroductionStroke is potentially preventable through risk factor reduction. Over the past decade, the role of microalbuminuria (MA) as a risk factor for chronic diseases has become apparent. The aim of this study was to determine the prognostic value of MA in acute stroke patients.Materials and methodsPatients with acute ischemic stroke admitted to our stroke unit were included in this study. Clinical history and vascular risk factors were recorded. Severity of stroke and outcome were assessed by NIHSS and modified Rankin scale (mRS) upon admission and discharge. Urinary albumin excretion was measured in 24-h urine samples. Multivariate analysis was performed to investigate predictors of poor outcome.ResultsMA was found in 43% of 138 patients and was associated with elevated levels of C-reactive protein (CRP), glucose at baseline, and HbA1c; higher rates of diabetes mellitus and atrial fibrillation; higher systolic blood pressure; greater age; and higher premorbid mRS, NIHSS upon admission/discharge, and mRS upon discharge. In a multivariate analysis, MA (OR 5.07, 95%CI 2.18-11.77; p = 0.004), premorbid mRS (OR 2.030, 95%CI 1.369-3.011; p = 0.0001), and NIHSS upon admission (OR 1.116, 95%CI 1.044-1.193; p = 0.001) were independent predictors of poor outcome upon discharge.ConclusionMA was frequently found in acute ischemic stroke patients. It was associated with severe neurological deficit upon admission and severe functional impairment upon discharge. MA in the acute phase was shown to be an independent predictor of poor outcome. The association between MA and CRP levels points to potential linkage of MA to the inflammatory response in acute stroke.